Expressão imunoistoquímica de GLUT-1 e marcadores de proliferação e apoptose em anomalias vasculares orais - Silva Filho, Tiago João da (2014)
Vascular anomalies constitute a distinct group of lesions, but they may present similar clinical and histopatological characteristics, which can lead to diagnostic mistakes. This study aimed by histopathology and immunohistochemical expression of human glucose transporter protein (GLUT-1), correctly identify and classify oral vascular anomalies, besides analyzing the immunoexpression of markers proliferation and apoptosis (Ki-67 and Bcl-2). All cases diagnosed as "oral hemangiomas" belonging to the archives of the Service of Pathological Anatomy from the subject of Oral Pathology of the Department of Dentistry (DOD), of the Federal University of Rio Grande do Norte (UFRN) were reviewed, totalizing 77 cases. Immunohistochemical analysis for GLUT-1 showed that only 26 (33.8%) of the specimens were true infantile hemangiomas (IHs). The 51 (66.2%%) GLUT-1 negative specimens were then reclassified as pyogenic granulomas (PGs) and vascular malformations (VMs) from their histopathologic characteristics,totalizing 26 (33.8%) cases of IHs, 20 (26.0%) of PGs and 31 (40.2) cases of oral VMs. The cases analyzed by the marker Ki-67 showed different median IH (13,85), PG (33,70) and VM (4.55) with statistically significant differences between them (p <0.001). In relation to the protein Bcl-2, the groups also showed different median of the established scores IH (1.00), PG (1.50), VMs (0.0) demonstrating statistically significant differences between them (p<0,001). No statistically significant correlation between the indexes of positivity for Ki-67 and the scores of immunoexpression of Bcl-2 were observed in any group. Thus, we can conclude that it is necessary a careful and parameterized review of cases of vascular anomalies making use of auxiliary tools such as GLUT-1, since the histopathological findings alone, sometimes, are not sufficient to differentiate some anomalies. Furthermore, analysis of the expressions of markers involved in the levels of proliferation of lesions is important for a better understanding of its biological behavior aspect